1995
DOI: 10.2307/2160937
|View full text |Cite
|
Sign up to set email alerts
|

Reflexivity of Tensor Products of Linear Transformations

Abstract: Abstract. Let A and B be linear transformations on finite-dimensional Hubert space. We characterize the reflexivity of A ® B in terms of certain characteristics of A and B .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, the singleton sequence 5 can be lengthened to the reflexive sequences 5,4; 5,5; and 5,6. On the other hand, the only two-term reflexive extension of the Jordan sequence (5,7) is (5,7), (5,7). Even the three-term reflexive extensions of (5, 7) are limited.…”
Section: Suppose That (Ab) Is a Double Commuting Pair With Corresponmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the singleton sequence 5 can be lengthened to the reflexive sequences 5,4; 5,5; and 5,6. On the other hand, the only two-term reflexive extension of the Jordan sequence (5,7) is (5,7), (5,7). Even the three-term reflexive extensions of (5, 7) are limited.…”
Section: Suppose That (Ab) Is a Double Commuting Pair With Corresponmentioning
confidence: 99%
“…In Proposition 6.4, we showed that the tensor product of two nilpotent operators is always reflexive. As discussed in [7], the situation is much more complicated when the hypothesis of nilpotence is dropped. From the point of view of Theorem 7.4, the problem arises from the failure of idempotents in stf(a®b) corresponding to points in a(a (x) b) to be simple tensor products of idempotents in s/(a) and sJ(b).…”
Section: An Operator Algebra Is Semisimple If and Only If It Is Similmentioning
confidence: 99%